1985
DOI: 10.1042/bst0130411
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cellulase biosynthesis and secretion in fungi

Abstract: press 23 1 61 -64 400 408 Microhiol. 34, 777 782 289-301 Vol. 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 14 publications
(17 reference statements)
0
19
0
1
Order By: Relevance
“…The synthesis of various catabolic enzymes in micro-organisms is repressed when glucose or other readily metabolizable compounds are added to the culture. In Trichoderma viride (Nisizawa et al, 1972) and Trichoderma reesei (Merivouri et al, 1985) the formation of some hydrolases, including a-amylase, P-glucosidase, xylanase and cellulase, was affected by glucose. This phenomenon has been called the glucose effect (Epps & Gale, 1942), or catabolic repression (Neidhardt, 1960;Holzer, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of various catabolic enzymes in micro-organisms is repressed when glucose or other readily metabolizable compounds are added to the culture. In Trichoderma viride (Nisizawa et al, 1972) and Trichoderma reesei (Merivouri et al, 1985) the formation of some hydrolases, including a-amylase, P-glucosidase, xylanase and cellulase, was affected by glucose. This phenomenon has been called the glucose effect (Epps & Gale, 1942), or catabolic repression (Neidhardt, 1960;Holzer, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…al ., 1984), and 0-glycosylation appears to be obligatory for their secretion (Merivuori et al, 1984;Messner & Kubicek, 1988;Kubicek et al, 1987). We have recently shown that 0-glycosylation in T. reesei (Kruszewska et al, 1989) proceeds in a similar way to that in yeasts (Tanner & Lehle, 1987), and may be controlled at the level of Dol-P or GDP-mannose supply.…”
Section: Introductionmentioning
confidence: 98%
“…However, during growth on this carbon source, mycelia cannot be separated from the insoluble cellulose, and hence preparation of mycelial subcellular fractions is difficult. In the present study we have therefore made use of a soluble carbon source (lactose) that is metabolized only slowly by T. reesei; this relieves the fungus from carbon catabolite repression and allows secretion of cellulases (Merivuori et al, 1984). Controls using glycerol (which does cause catabolite repression) as carbon source were included.…”
Section: Stimulation Of T Reesei Cellulase and Protein Secretion Bymentioning
confidence: 99%
“…We have recently presented evidenice that low levels of a conidial endoglucanase and a plasma membrane-boundglucosidase are involved in cellulase induction in T. reesei QM9414 (15). The latter enzyme has been shown to form sophorose-the putative in vivo inducer (8,15,20,21,22,26,34,35)-in vitro (8). The mechanism of carbon catabolite repression has not been dealt-with; it has only been shown that it is not restricted to the presence of glucose but can be observed with several other sugars or glucose metabolites (25).…”
mentioning
confidence: 99%